ANALISIS KERAPATAN EKOSISTEM MANGROVE DI PULAU PANIKIANG DAN DESA TONGKE-TONGKE SULAWESI SELATAN - Andi Nur Samsi; Sharifuddin Bin Andy Omar; Andi Niartiningsih (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2018)
The mangrove ecosystem has different density levels per location. It can be influenced by environmental factors or because of human assistance. This research was conducted in Tongke-tongke Village, Sinjai Regency and Pannikiang Island, Barru District. Observations were conducted on three groups, namely groups of trees, stakes, and seedlings. Tree group used plot size 10 m x 10 m, stakes group used plot size 5m x 5m, and the group of seedlings used plot size 1 m x 1m. The result of tree group density will be compared with the standard criteria of mangrove damage of the Minister of Environment to know the criteria and the level of density. The mangrove ecosystem in Tongke-tongke village is overgrown by Rhizophora mucronata and Avicennia sp. and is dominated by R. mucronata with very dense density. In the tree group, R. mucronata has a density of 8020 Ind Ha-1. The mangrove ecosystem in Pannikiang Island is overgrown with Rhizophora apiculata, Rhizophora stylosa, Sonneratia alba, Aegiceras floridum, Ceriops tagal, Avicennia sp., Excoearia agallocha, and Lumnitzera racemosa and has a rare and moderate density. In the tree group, the highest density in C. tagal with a density of 1270 Ind Ha-1 and indicated moderate density. Competition is always there in the ecosystem. The species of this ecosystem is fighting for space and nutrients. Therefore, competition can determine the density of plants in it.